Anti-inflammatory activity of polyphenolics from açai (Euterpe oleracea Martius) in intestinal myofibroblasts CCD-18Co cells. Issue 10 (5th August 2015) - Dias, Manoela Maciel dos Santos; Martino, Hércia Stampini Duarte; Noratto, Giuliana; Roque-Andrade, Andrea; Stringheta, Paulo César; Talcott, Stephen; Ramos, Afonso Mota; Mertens-Talcott, Susanne U.
Abstract : This is the first time that the anti-inflammatory activities of açai polyphenols relevant to intestinal inflammation were demonstrated in colon fibroblasts cells. Abstract : The demand for tropical fruits high in polyphenolics including açai ( Euterpe oleracea Mart.) has been increasing based on ascribed health benefits and antioxidant properties. This study evaluated the anti-inflammatory activities of açai polyphenolics in human colon myofibroblastic CCD-18Co cells to investigate the suppression of reactive oxygen species (ROS), and mRNA and protein expression of inflammatory proteins. Non-cytotoxic concentrations of açai extract, 1–5 mg gallic acid equivalent L −1, were selected. The generation of ROS was induced by lipopolysaccharide (LPS) and açai extract partially reversed this effect to 0.53-fold of the LPS-control. Açai extract (5 mg GAE L −1 ) down-regulated LPS-induced mRNA-expression of tumor necrosis factor alpha, TNF-α (to 0.42-fold), cyclooxygenase 2, COX-2 (to 0.61-fold), toll-like receptor-4, TLR-4 (to 0.52-fold), TNF receptor-associated factor 6, TRAF-6 (to 0.64-fold), nuclear factor kappa-B, NF-κB (to 0.76-fold), vascular cell adhesion molecule 1, VCAM-1 (to 0.71-fold) and intercellular adhesion molecule 1, ICAM-1 (to 0.68-fold). The protein levels of COX-2, TLR-4, p-NF-κB and ICAM-1 were induced by LPS and the açai extract partially reversed this effect in a dose-dependent manner. These results suggest the anti-inflammatory effect of açai polyphenolic extract in intestinal cells are at least in part mediated through the inhibition of ROS and the expression of TLR-4 and NF-κB. Results indicate the potential for açai polyphenolics in the prevention of intestinal inflammation.